Adherence to a Mediterranean Diet is associated with physical and cognitive health: A cross-sectional analysis of community-dwelling older Australians - Allcock, Lisa; Mantzioris, Evangeline; Villani, Anthony (Frontiers in Public Health, 2022)
Poor cognitive function is associated with reduced functional independence, risk of institutionalization and reduced health-related quality of life. The ability to independently perform instrumental activities of daily living (iADLs) is compromised in patients with mild cognitive impairment (MCI) or dementia. Emerging evidence suggests that adherence to a Mediterranean diet (MedDiet), may play an important protective role against cognitive decline and dementia risk, whilst preserving functional status. This cross-sectional study aimed to explore the independent associations between MedDiet adherence, cognitive risk, and functional status in community-dwelling older adults living in Australia. MedDiet adherence was assessed using the Mediterranean Diet Adherence Screener (MEDAS); a modified Lawton's iADL scale was used for the assessment of functional status and risk of cognitive impairment was assessed using the AD8 dementia screening intervention. A total of n = 294 participants were included in the final analyses (70.4 ± 6.2 years; Females, n = 201; Males, n = 91; n = 2 unspecified). Adherence to a MedDiet was positively associated with functional ability (β = 0.172; CI: 0.022, 0.132; P = 0.006) independent of age, gender, Body Mass Index (BMI), smoking status, sleep duration, physical activity duration, diabetes status, and level of education. Furthermore, MedDiet adherence was inversely associated with cognitive risk (β = −0.134; CI: −0.198, −0.007; P = 0.035) independent of all covariates. However, our sensitivity analyses further showed that adherence to a MedDiet was not associated with cognitive risk in older adults free from cognitive impairment. We showed that adherence to a MedDiet is associated with healthy physical and cognitive aging. Nevertheless, exploration of these findings in larger cohorts, using longitudinal analyses and controlling for important confounders to ascertain the direction of the relationship is warranted.